An-Nahar newspaper and the limits of freedom and secrecy in publishing in the debates of the House of Representatives, the decisions of the Algiers Conference 1973 “a model”. (Journal of Misan Researches, 2022)
There is no doubt that the Lebanese press is at the forefront of the Arab press, and that the freedom of the press distinguished the Lebanese society from its regional environment, but what is the extent of that freedom? Is it absolutely unrestricted? Does the press have the right to publish anything that would harm the country's supreme interest? An-Nahar newspaper published (secret) decisions that the Arabs had decided at the Sixth Arab Summit held in Algeria for the period from November 26-28, 1973. This caused a state of discontent in official and popular circles, and the issue was discussed because of its importance in the House of Representatives.    In order to reveal the mysteries of the subject, and to know the boundary between freedom and confidentiality in press publication, we chose for our research a title ((Al-Nahar newspaper and the limits of freedom and secrecy in publishing in the debates of the House of Representatives, the decisions of the Algiers Conference 1973 “a model”)).